Artificial intelligence literacy in sustainable development: A learning experiment in higher education - Alamäki, Ari; Nyberg, Crister; Kimberley, Anna; Salonen, Arto O. (Frontiers in Education, 2024)
Challenges related to sustainable development are enormous, and the effects of viable solutions are hard to grasp. The assistance of AI potentially creates opportunities for developing solutions supporting sustainable development. However, utilizing this potential requires AI literacy. In this task higher education (HE) plays a significant role. Although both AI and sustainable development are present in HE curricula their execution is complicated. The purpose of this empirical research was to map the capabilities and perceptions of undergraduate business administration students about artificial intelligence and its potential to answer questions related to sustainability transition in society, and to obtain information about the suitable pedagogical solutions for increasing the knowledge and understanding related to these themes. The data was gathered in a workshop that consisted of introductory lecture, answering surveys, group discussions, and personal reflections on the relationship and possibilities of artificial intelligence and sustainable development. In data analysis, we adopted an abductive qualitative research methodology. Through abduction, we obtained new insights and created new knowledge regarding AI literacy in the context of sustainable development. This brought new knowledge in the context of HE studies. The taxonomy of AI literacy in sustainable development created a new reference framework for learning tasks, and course planning in HE. The results showed that the students had difficulties solving the actual problem because they lacked knowledge and understanding of the basics of artificial intelligence and sustainable development. However, in groups where even one person had a deeper understanding of the concepts, the whole group began to understand the task and work on both meta-level ethical questions and practical examples.